The effects of two-versus three-dimensional visual aids on the achievement and attitude of chemistry students - Negre, Alma S. (1990)
The learning-teaching process is a matter of personal initiative and personal response. This study compared the performance of students exposed to teaching with two- and three-dimensional visual aids. The samples involved were 45 third year high school students of Camiguin National High School. The instruments used to gather data were a 43-item Chemistry Achievement Test and an Attitude Inventory using 18 Likert-type statements. The following conclusions were drawn from the study: the use of 2D and 3D visual aids in teaching did not significantly affect the achievement of students in chemistry; there was no interaction effect between the use of 2D or 3D visual aids and the IQ of students; and the use or non-use of visual aids did not affect the attitude of students toward chemistry.